"WALANG-WALA" ("Nothing is left"): Rituals for Collective Grieving, Disaster Memory, and Social Repair. Issue 2 (3rd July 2017) - Go, Chaya Ocampo
Abstract : Super typhoon Yolanda (internationally named Haiyan)—the strongest storm in recorded history—ravaged through the Visayan Islands of the Philippines on 8 November 2013. In this article I examine the transformative power of collective grieving in translocal and transnational contexts postdisaster. Having served as a disaster relief worker across the Visayas, and now writing as a transnational Filipina scholar, I inquire: How is disaster memory shared from body to body, from the geographical margins of a nation-state to the rest of an archipelago, and across the ocean to global diasporas? How might acts of remembering and grieving together enable new forms of political agency in the wake of a super typhoon? In exploring the relationship between disaster memory and social repair, I consider the creation of ritual as an art practice, performance, and protest. I outline how my creative-critical engagement with ritual in three different forms has facilitated the co-creation of spaces for the individual to grieve together with the collective. This series of projects, together called " WALANG-WALA, " explores the embodiment and experience of a state of absolute emptiness and nothingness one is left with after catastrophic disasters such as Yolanda. In these rituals, I approach disaster memory as a cultural practice of collective and active remembering of what we love and lost.